Fieldoffice Architects In Situ: Reflecting on the Rural‐Urban Mix in Yilan, Taiwan. (July 2016) - Huang, Sheng‐Yuan; Hung, Yu‐Hsiang
Abstract : Yilan is generally considered a rural county with a city at its heart. Fieldoffice Architects, whose team live and work entirely in this area and are deeply immersed in its community, take a more holistic view. Their collaborative approach blurs the boundaries between rural and urban, with architecture and environmental design projects interconnecting to form part of a regional framework. PrincipalSheng‐Yuan Huang and Project ArchitectYu‐Hsiang Hung reflect on their practice.